Pelaksanaan Parenting Pendidikan Seks (Pesek) Anak Usia Dini di PAUD Tunas Bangsa Ungaran Kabupaten Semarang - Tritjahjo Danny Soesilo (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
The purpose of this research is to identify the implementation and the needs of sex education for early childhood pupils in preschool so that it could be used to make parenting models for early childhood sex education to meet schools and parents’ needs. This study included a qualitative descriptive study conducted for 1 semester. The subject of this study are teachers at Tunas Bangsa PAUD, Merpati Ungaran Cluster, Semarang District. The data collection techniques used are interviews and questionnaires. The data were analyzed using qualitative descriptive. The result showed that teachers had not been doing sex education for early childhood intensely because they did not understand the material in detail about sex education. The school has never carried out parenting activities about sex education for children but actually require parenting for early childhood sex education by bringing the experts. The parenting of sex education are expected in the form of seminars and counseling, or in the form of games thus they can involve parents and able to carry that task in pleasant conditions.